The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2014
DOI: 10.2117/psysoc.2014.49
|View full text |Cite
|
Sign up to set email alerts
|

Beautiful Faces Enhance Verbal Working Memory Performance: An Nirs Study

Abstract: In addition to material rewards (such as money, food, and liquid), various social signals, including facial attractiveness, are perceived as incentives. Although material and monetary rewards are known to enhance various aspects of cognitive performance, it is not clear whether and how social signals affect cognition. The present study focused on facial attractiveness and investigated its effects on working memory. In addition, we used near-infrared spectroscopy (NIRS) to characterize the activation in the dor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 27 publications
1
3
0
Order By: Relevance
“…However, because the photographs are attractive, it may be useful to “remember” them, even though falsely. Considering previous research, it seems that we have to agree with those claiming that attractive stimuli have an advantage in enhancing memory recognition – such as Cross et al (1971) , Kajimura et al (2014) and others ( Marzi and Viggiano, 2010 ; Tsukiura and Cabeza, 2011 ; Zhang et al, 2011 ) – while also agreeing with those claiming that the accuracy of that recognition is lower for attractive stimuli ( Light et al, 1981 ; Sarno and Alley, 1997 ; Wiese et al, 2014 ).…”
Section: Discussionsupporting
confidence: 80%
See 2 more Smart Citations
“…However, because the photographs are attractive, it may be useful to “remember” them, even though falsely. Considering previous research, it seems that we have to agree with those claiming that attractive stimuli have an advantage in enhancing memory recognition – such as Cross et al (1971) , Kajimura et al (2014) and others ( Marzi and Viggiano, 2010 ; Tsukiura and Cabeza, 2011 ; Zhang et al, 2011 ) – while also agreeing with those claiming that the accuracy of that recognition is lower for attractive stimuli ( Light et al, 1981 ; Sarno and Alley, 1997 ; Wiese et al, 2014 ).…”
Section: Discussionsupporting
confidence: 80%
“…However, they have brought mixed results. Whereas some researchers reported more accurate memory for attractive stimuli (e.g., Cross et al, 1971 ; Allan et al, 2012 ; Kajimura et al, 2014 ), others found the opposite ( Light et al, 1981 ; Sarno and Alley, 1997 ; Wiese et al, 2014 ), some did not obtain a difference in memory accuracy ( Brigham, 1990 ; Wickham and Morris, 2003 ; Anderson et al, 2010 ) and others obtained a mixture of both ( Deblieck and Zaidel, 2003 ). It also seems that, compared with males, females are better at remembering same-sex faces when faces of both sexes are presented ( Rehnman and Herlitz, 2007 ; Wang, 2013 ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Forty-two channels of an fNIRS system (FOIRE-3000, Shimadzu Corporation, Kyoto, Japan) were used in the present study (Kajimura et al, 2014 ). This system operates at three wavelengths (780 nm, 805 nm and 830 nm; Zhu et al, 2014 ).…”
Section: Methodsmentioning
confidence: 99%